Factors that determine mental health professionals’ decision to support home-based video consultations – A qualitative study - Moeller, Anne Marie; Hansen, Jens Peter; Andersen, Pernille Tanggaard (Frontiers in Psychiatry, 2022)
Introduction: Using videoconferencing for consulting with patients in the mental health services has been shown in interventions to be similarly effective as when meeting in person. In practice, it often makes more sense to use video consultations with patients in a more flexible way than interventions permit. The aim of this study was to investigate what constitutes a professional video consultation from the perspectives of mental health professionals and explore what is of importance for the establishment and realization of video consultations in practice. Methods: A Grounded Theory methodology approach based on Corbin and Strauss was used. Data collection consisted of participant observations of introductory events followed by individual interviews with mental health professionals who had used video consultations with patients. Findings: Mental health professionals believed that a professional video consultation was one that was not inferior to an in-person consultation but offered something else, such as more and easier access, accommodating patients’ needs and wishes. At the same time, it should not interfere with the treatment quality, e.g., by hampering communication and therapeutic tasks. The expected treatment quality was based on an individual assessment of the patient and varied from clinician to clinician. The implementation process and support which the organization provided affected the clinicians’ attitudes as well as the clinicians’ experiences and hence how the clinicians assessed the quality of the service. Conclusion: Perceived usefulness, patient demands, and close IT support will positively impact the establishment and realization of video consultations whereas high workload and technical problems would hamper it.